The Extent of Geography Teachers' Use of Visual Thinking Skills in ‎Teaching - Buthaina Mohammed Jasem; Moussa K. Hanna (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: The current study aimed to: identify the extent to which geography teachers use visual thinking skills in teaching; examine the differences in responses of the sample regarding the use of visual thinking skills by geography teachers according to gender and teaching experience; and determine the level of visual thinking skills among second-grade intermediate students in geography and the differences between them according to gender. Methodology: The study adopted the descriptive analytical approach. The sample consisted of 41 teachers (23 male teachers and 18 female teachers). Five students were randomly selected from each teacher to apply the visual thinking test, resulting in a student sample of 205 (115 male students and 90 female students). A questionnaire for geography teachers was developed, consisting of 25 items divided into five skills: inferring meaning, recognizing visual shapes, analyzing visual shapes, interpreting information from visual shapes, and visual differentiation. A visual thinking test was also developed, consisting of 25 items divided into the same five skills. The validity and reliability of both the questionnaire and the test were verified. Results: After analyzing the data, the results showed that geography teachers reported a relatively weak practice of visual thinking skills. The results also showed that geography teachers’ awareness of visual thinking skills and their development for students during geography lessons was somehow limited. Finally, there was an average level of visual thinking skills among second-grade intermediate students.